COMPARATIVE STUDY OF DEMONSTRATIVES IN SASAK AND CHINESE - Sutarman, NFN; Abdussamad, Zainudin; Muhid, Abdul; Supatmiwati, Diah; Suktiningsih, Wiya (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
Demonstratives in Chinese and Sasak languages have semantically and syntactically significant different concepts. Semantically, The Chinese language applies a two-way system consisting of proximal ‘zhe/zh’e and distal ‘na/nei’while Sasak language particularly the Menu-Meni dialect uses a three-way system including proximal‘ne’, medial‘tie’, and distal‘nu’. Syntactically, demonstrative in Chinese is categorized into five subtypes: pronominal, adnominal, locational, temporal, manner, and degree. Sasak, on the other hand, includes pronominal, adnominal, identificational, adverbial, verbal, quantificational, and referential. This paper shows that the Chinese and Sasak languages has semantically similar in the concept of proximity and different in medial and distal one. Syntactically, these languages have nominal and adverbial demonstrative which share similar properties but differ in other demonstrative categorizations. Demonstratif dalam bahasa Cina dan bahasa Sasak memiliki perbedaan konsep yang signifikan secara semantik dan sintaksis. Secara semantik, bahasa Cina menerapkan sistem dua arah yang terdiri dari proksimal 'zhe/zh'e dan distal 'na/nei' sedangkan bahasa Sasak khususnya dialek Menu-Meni menggunakan sistem tiga arah meliputi proksimal 'ne', medial 'tie', dan distal 'nu'. Secara sintaksis, demonstratif dalam bahasa Cina dikategorikan menjadi lima subtipe: pronominal, adnominal, locational, temporal, Manner, dan degree. Sasak, di sisi lain, memiliki pronominal, adnominal, identificational, adverbial, verbal, Quantifier, referential. Tulisan ini menunjukkan bahwa bahasa Cina dan bahasa Sasak secara semantik memiliki kesamaan dalam konsep proximity dan berbeda dalam konsep medial dan distal. Secara sintaksis, bahasa-bahasa ini memiliki demonstratif nominal dan adverbial dengan ciri yang sama tetapi berbeda dalam kategorisasi demonstratif lainnya.